Implementasi Program Keluarga Harapan Dalam Penanggulangan Kemiskinan Di Kecamatan Kutawaluya Kabupaten Karawang - Rizky Chandra Moekti; Gili Argenti; Rachmat Ramdani (Jurnal Ilmiah Wahana Pendidikan, 2022)
The title of this research is the implementation of the Family Hope Program in poverty alleviation in Kutawaluya sub-district, Karawang district This research was carried out using a qualitative descriptive method. data sources consist of: primary data sources and secondary data sources, primary data sources obtained from observations, and interviews with informants (purposive sampling) based on interview guides as instruments, researchers as research instruments. secondary data obtained from the documentation. data analysis using the George C. Edwards III model whose activities include: Communications (Communications), resources (resources), attitudes (dispositions or attitudes) and bureaucratic structure (bureucratic structure).